Numerical and Analytical Simulations of Nonlinear Time Fractional Advection and Burger's Equations. (6th October 2022) - Khan, Hassan; Khan, Qasim; Tchier, Fairouz; Ibrarullah,; Hincal, Evren; Singh, Gurpreet; Tawfiq, F. M. O.; Khan, Shahbaz
Abstract : In this paper, the higher nonlinear problems of fractional advection-diffusion equations and systems of nonlinear fractional Burger's equations are solved by using two sophisticated procedures, namely, the q-homotopy analysis transform method and the residual power series method. The proposed methods are implemented with the Caputo operator. The present techniques are utilised in a very comprehensive and effective manner to obtain the solutions to the suggested fractional-order problems. The nonlinearity of the problem was controlled tactfully. The numerical results of a few examples are calculated and analyzed. The tables and graphs are constructed to understand the higher accuracy and applicability of the current method. The obtained results that are in good contact with the actual dynamics of the given problem, which is verified by the graphs and tables. The present techniques require fewer calculations and are associated with a higher degree of accuracy, and therefore can be extended to solve other high nonlinear fractional problems.